FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN LEPTOSPIROSIS DAN PENCEGAHANNYA (REVIEW) - St. Aisyah Sijid; Cut Muthiadin; Zulkarnain Zulkarnain; Risdayanti Adi Purba (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2022)
Leptospirosis is a zoonotic disease caused by the bacteria Leptospira which is transmitted by mice. This disease is found in tropical and subtropical regions that have high rainfall. Leptospira bacteria can infect humans through skin wounds or mucous membranes such as the nose, mouth and eyes. The aim is to determine the factors that influence the incidence of leptospirosis and how to prevent it. The factors that influence the incidence of leptospirosis are the presence of standing water, the condition of the gutters, the presence of rats, activity in water and a history of wounds. Prevention of leptospirosis can be done by providing counseling, protecting workers, recognizing potentially contaminated water and soil, eradicating rodents (rats), separating infected pets, vaccinating livestock and pets, vaccines and covering wounds and abrasions with waterproof dressings.